2010
DOI: 10.5014/ajot.2010.09198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Tailored Activity Pacing Intervention on Pain and Fatigue for Adults With Osteoarthritis

Abstract: Objective We examined whether a tailored activity pacing intervention was more effective at reducing pain and fatigue than a general activity pacing intervention. Method Adults with knee or hip osteoarthritis (N = 32) stratified by age and gender were randomized to receive either tailored or general pacing instruction. Participants wore an accelerometer for five days that measured physical activity and allowed for repeated symptom assessment. Tailoring involved using data from the accelerometer. Outcomes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 19 publications
3
102
0
Order By: Relevance
“…5,8,14 However, this finding contrasts previous associations between pacing and reduced pain. [43][44][45] More unexpected was the significant association between Activity progression and increased pain. It is suggested that participants who progress their activities experience natural increases in symptoms related to increased exertion.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…5,8,14 However, this finding contrasts previous associations between pacing and reduced pain. [43][44][45] More unexpected was the significant association between Activity progression and increased pain. It is suggested that participants who progress their activities experience natural increases in symptoms related to increased exertion.…”
Section: Discussionmentioning
confidence: 88%
“…46 Pacing was defined as adaptive pacing therapy in the PACE trial which may be similar to the themes Activity adjustment, Activity acceptance and some facets of Activity planning. Notably, neither Murphy et al 43 or White et al 46 implemented a pacing scale.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Activity pacing is defined as "a strategy in which people strive not to exacerbate their symptoms by planning both daily activities and rest breaks and by segmenting tasks into multiple shorter time blocks" (27). Within this strategy, slowing down and spending more time was the action most frequently stated by the participants (Table V).…”
Section: Self-managementmentioning
confidence: 99%
“…(15), (2) "Effects of a tailored activity pacing intervention on pain and fatigue for adults with osteoarthritis." (16), (3) "Positive affect mediates the relationship between pain-related coping efficacy and interference in social functioning. The journal of pain : official journal of the American Pain Society" (17) e (4) …”
Section: Avaliação Da Qualidade Da Informação Dos Estudos Elegíveismentioning
confidence: 99%